Impact of Short‐Term Climate Variability on Volatile Organic Compounds Emissions Assessed Using OMI Satellite Formaldehyde Observations. Issue 16 (30th August 2018) - Stavrakou, T.; Müller, J.‐F.; Bauwens, M.; De Smedt, I.; Van Roozendael, M.; Guenther, A.
Abstract: A major feedback between climate and atmospheric chemistry lies in the meteorological dependence of the emissions of biogenic volatile organic compounds (BVOCs), precursors of important climate forcers, aerosols, and ozone. Whereas the short‐term response of BVOC emissions to meteorological drivers is fairly well simulated by current emission models, it is yet unclear whether models can faithfully predict their response to climate change, given the scarcity of long observation records of BVOC fluxes. Here we take advantage of the high yield of formaldehyde (HCHO) in the oxidation of VOCs and use a long‐term spaceborne record of HCHO observations in combination with model simulations to show that (i) HCHO interannual variability is primarily driven by climate through its impacts on photochemistry, vegetation fire occurrence, and above all, biogenic emissions and (ii) the HCHO record validates the interannual variability of biogenic emissions calculated by the state‐of‐the‐art Model of Emissions of Gases and Aerosols from Nature (MEGAN) emission model in vegetated regions. Plain Language Summary: This study is motivated by the incomplete knowledge of a major feedback between climate and atmospheric chemistry lying in the meteorological dependence of the emissions of biogenic volatile organic compounds into the atmosphere. Although the short‐term response of biogenic fluxes to meteorological drivers is relatively well established, their long‐term response is not yet assessed due to the lack of long‐term observation records of biogenic fluxes. Here we address two fundamental questions: (i) Can we assess the long‐term response of biogenic fluxes to meteorological fields? (ii) Does a widely used biogenic emission model (MEGAN) provide reliable predictions of how those fluxes might respond to climate change? In this study, and for the first time, the long‐term variability of hydrocarbon emission fluxes is assessed by using a long‐term spaceborne formaldehyde data set (2005–2015). Analysis of this unique observational record and of multiyear model simulations reveals clear evidence that (i) the observed interannual variability is primarily driven by climate through its impacts on biogenic emissions and photochemistry, (ii) the formaldehyde data record validates the long‐term response of biogenic emissions to climate variability predicted by the MEGAN state‐of‐science biogenic emission model, and (iii) the predicted biogenic emission trends appear consistent with the formaldehyde data record. Key Points: Eleven years of OMI formaldehyde observations were used to assess the long‐term response of biogenic emissions to climate changes The interannual HCHO variability is primarily driven by climate through its impacts on biogenic fluxes, photochemistry, and fire occurrence The OMI HCHO record validates the interannual variability of biogenic emissions calculated by the state‐of‐the‐art MEGAN emission model